Analysis of Students' Mathematical Problem-Solving Abilities on Algebraic Fraction Multiplication Material Who Learned Using Problem Based Learning in Class VII SMP N 3 Kisaran - Fazariah, Nur Aisiyah; Rahmadani, Elfira; Masithoh, Ety (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
Problem solving ability is one of the important key skills in mathematics which is suitable to be combined with the Problem Based Learning learning model. This research aims to describe the mathematical problem-solving abilities of students who have high, medium and low mathematical abilities in the material of multiplication of algebraic fractions at SMPN 3 Kisaran located in Asahan district, North Sumatra. This research uses descriptive qualitative, namely a type of research that aims to describe phenomena or events observed in detail and in depth. This research method often uses data collection techniques in the form of test results on problem solving abilities per indicator. The results of research from 32 students showed that the high group consisted of 9 students with a percentage of 28.125%, the medium group had 18 students with a percentage of 56.25%, and the low group consisted of 5 students with a percentage of 15.625%.